Pertumbuhan dan Hasil Tanaman Sayuran Daun Sistem Hidroponik Dengan Nutrisi Pupuk Organik Cair Berbagai Sisa Buahan - Teguh Achadi; Maria Fitriana; Marlina Marlina; Fitra Gustiar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Achadi T, Fitriana M, Marlina M, Gustiar F. 2021. Growth and yield leaf vegetables cultivated hydroponic with nutrition liquid organic fertilizer of kind leftover fruits. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 924-930. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Liquid organic fertilizer is the result of overhaul or decomposition of organic matter, can come from animals or plants. Liquid organic fertilizer is made from damaged or rotten fruit and skin fruit (bananas, papayas, pineapples and a mixture of all three). So far, the hydroponic system uses inorganic nutrients or fertilizers (for example AB mix). This study aims to find out the effect of liquid organic fertilizers (POC) on the growth and yield of leaf vegetables (kale, spinach and caisim).This research used a hydroponic system, carried out from July to September 2021. This study used completely randomized design, with 8 treatments and 4 replications? The treatments were A = AB mix, B = liquid organic fertilizer from bananas, C = liquid organic fertilizer from pineapples, D = liquid organic fertilizer from papaya, E = liquid organic fertilizer from bananas and pineapples, F = liquid organic fertilizer from bananas and papayas, G = liquid organic fertilizer from pineapple and papayas, H = liquid organic fertilizer from bananas, pineapples and papayas. The results showed that liquid organic fertilizer had not been able to replace the AB mix solution, but there was hope liquid organic fertilizer could replace AB mix solution although the growth of spinach plants given POC leftover papaya fruit and POC fruit mixture (Pineapple + Papaya) shows growth, while caisim and kale plants show better growth than spinach plants. The remaining POC of pineapple fruit encourages the growth of caisim plants while poc of papaya fruit remains encourage the growth of kale plants.